Effects of auxin and cytokinin on callus induction in Catharanthus roseus (L.) G. Don - Abdul Rahman, Natrisya Nur; Rosli, Rozita; Kadzimin, Saleh; Hakiman, Mansor (Farm to Fork Foundation, 2019)
The study was conducted to observe the effect of different concentration and combination of auxin and cytokinin towards the callus induction of C. roseus. Explants comprising of basal leaf with petioles of Catharanthus roseus were cultured onto MS media supplemented with different types and concentrations of auxins (naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic (2,4- D)) and cytokinins (benzyl amino purine (BAP), and kinetin). Calli produced from explants showed differences in response in each of the treatment combinations. Treatments with kinetin and NAA, BAP with 2,4-D (Experiment B) did not differ significantly. Treatment with 3.0 mg L−1 BAP + 3.0 mg L−1 NAA (Experiment C) gave the highest dry weight (2.776 g) suggesting an optimum level of combination for callus induction.